Methodological guidelines to assist women victims of violence. - Laura Magda López Angulo (Medisur)
Women abuse is an obstacle to achieve equality, development, peace and social inclusion. This is a violation of human rights limiting their personal freedom and annulling their main warranties as their right to have security, integrity and even life. In the 90´ it has been identified as a health problem due to its frequency and severity, its magnitude and influence in health recovery. With the objective of supporting the decrease of this invisible plague from a Public Health perspective, we considered timely and pertinent to adjust a format of Methodological Guidelines aimed at setting rules and unifying procedures, including the complexity and implications of violence, based on the needs of each part.